Heart rate and activity profile for young female soccer players - Alvarez, J. C. B.; Lopez, M. G.; Alvarez, V. B.; Granda, J.; Castagna, C. (Journal of Human Sport & Exercise, 2008)
The physical and physiological demands of high-level male soccer have been studied extensively, while few studies have investigated the demands placed on females during match-play, however, there is no information available about the heart rate and activity profile of young female soccer players during match play. Therefore, the aim of this study was to examine cardiovascular (heart-rates HR) and physical demands of young female soccer players during a match. Players were observed during a friendly competitive match (7-a-side) over 2 x 25-min halves. Match activities were assessed with Global Position System technology (1Hz). Result showed that young female soccer players attain 88±4.4% and 86.3±4.8% of HRmax during the first and second half respectively (P=0.3), the average heart rate was 87%. During the first and second half, they covered 2072±197 m and 1905±144 m (P13 km/h) resulted lower than that previously reported for age-matched male soccer players and elite female soccer players. This seems to indicate that gender and competitive level differences in match physical performance seem to occur mainly in the absolute match work-rate domain.